Non‐neuronal kappa‐opioid receptor activation enhances epidermal keratinocyte proliferation, and modulates mast cell functions in human skin ex vivo. Issue 8 (14th June 2020) - Chéret, Jérémy; Gherardini, Jennifer; Soeberdt, Michael; Hundt, Jennifer E.; Abels, Christoph; Bertolini, Marta; Paus, Ralf
Abstract: Kappa‐opioid receptor (KOR) activation reportedly elicits anti‐inflammatory responses and can downregulate neuropeptide release from sensory nerve fibers. While this renders KOR agonists (KORAs) potentially interesting therapeutics in skin diseases associated with neurogenic inflammation, it remains poorly understood how KOR agonists impact on human skin and dermal mast cells (MCs) ex vivo, in the absence of functional innervation. The KORA 5a was administrated to the culture medium (200 nmol/L and 1 µmol/L) in human skin organ culture, thus mimicking a "systemic" mode of application. We show that KORA significantly increased epidermal thickness and upregulated the number and proliferation of epidermal keratinocytes. Unexpectedly, it also stimulated epidermal keratinocyte apoptosis in situ, compared with vehicle. Moreover, KORA significantly decreased the number of c‐Kit‐positive MCs, but did not significantly alter the number or degranulation of mature (tryptase‐ or toluidine blue‐positive) MCs. These pilot observations render the tested KORA (5a) an interesting candidate for the management of inflammatory dermatoses in which MC‐dependent neurogenic skin inflammation plays an important role (e.g. atopic dermatitis, psoriasis).